2017
DOI: 10.1037/pac0000205
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ourselves within intergroup conflict: The role of intragroup dialogue in promoting acceptance of collective narratives and willingness toward reconciliation.

Abstract: The current article presents a new intervention model for intragroup dialogue. Twenty-four Jewish-Israeli undergraduate students underwent a yearlong process to learn about the Israeli–Palestinian conflict, encountered Palestinian narratives, and reflected on the impact of the Palestinian other on their own identity as Jewish-Israelis. In this research we propose that such a process ameliorates identity threats posed by an intergroup conflict on collective identities, encouraging participants to adopt a more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
1
30
0
1
Order By: Relevance
“…Unlike the group process within the course which took place a year before in a different political context (see: Ben David & Idan, 2019; Ben David et al, 2017) in which the group discourse transformed from categorical and defensive to more complex and inclusive, the analysis of this year revealed that the group dynamic resembled an escalating circle. As it appeared, while the intensity of the discussion in terms of content (for example, surfacing of traumatic experiences and controversial issues) increased throughout the process, the rhetoric of the group discourse remained the same.…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…Unlike the group process within the course which took place a year before in a different political context (see: Ben David & Idan, 2019; Ben David et al, 2017) in which the group discourse transformed from categorical and defensive to more complex and inclusive, the analysis of this year revealed that the group dynamic resembled an escalating circle. As it appeared, while the intensity of the discussion in terms of content (for example, surfacing of traumatic experiences and controversial issues) increased throughout the process, the rhetoric of the group discourse remained the same.…”
Section: Literature Reviewmentioning
confidence: 90%
“…This understudied form of dialogue can be mainly found in the field of peace education (e.g., Salomon, 2004) and in recent initiatives (Rosenak, Leshem Zinger, & Isaacks, 2014). It has great potential in exploring the psychological implications of intergroup conflict on ingroup members' subjectivity (Ben David et al, 2017), particularly in how internal political discourse evolves within social groups (Ben David & Idan, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The program which continued for eight consecutive years was successful in turning the campus into a place which advances equal opportunities and dialogue between the national groups. Similarly, David et al (2017), using both qualitative and quantitative methods, studied twenty-four Jewish-Israeli undergraduate students who underwent a yearlong process to learn about the Israeli-Palestinian conflict, encountered Palestinian narratives, and reflected on the impact of the Palestinian other on their own identity as Jewish-Israelis. Results show that participants developed an increased capacity for acceptance of both Israeli and Palestinian collective narratives, and demonstrated a greater willingness toward reconciliation, manifested in more readiness to acknowledge alterity.…”
Section: Mid/short-term Intergroup Encountersmentioning
confidence: 99%
“…Ahora bien, si optamos por insistir en que la deconstrucción de narrativas colectivas es necesaria para avanzar hacia la reconciliación, los caminos que sugieren otras experiencias pasan por el contacto intergrupal, la humanización del otro y la toma de perspectiva (Ben et al, 2017;Ugarriza y Nussio, 2016). En este sentido, podríamos seguir las lecciones de recientes ejercicios en Serbia y Montenegro, en donde excombatientes serbios y croatas han visitado juntos distintos memoriales para discutir sus visiones sobre el conflicto y avanzar hacia la reconciliación (Moore, 2017).…”
Section: Dossier: Comisiones De La Verdad Históricas Y De Justicia Tunclassified